Trends and Sex Differences in Access to HIV Care with Scale Up of National HIV Treatment Guidelines in Pune, India. (22nd June 2020) - Raichur, Priyanka; Salvi, Sonali Pankaj; Sangle, Shashikala; Chavan, Amol; Nimkar, Smita; Gawande, Gajanan; Rewari, Bharat; Mathad, Jyoti; Mcintire, Katherine; Gupta, Amita; Marbaniang, Ivan; Mave, Vidya
Test and treat is the current global standard, yet sex differences persist in access to HIV care. We assessed the differences in presentation and antiretroviral therapy (ART) uptake by sex and ART-eligibility period among ART-naive adults registered at a public ART center in India. Four ART eligibility periods were defined by programmatically determined CD4 criteria (periods I-IV: CD4 <200, <350, ≤500 cells/μL, and any CD4) between January 2005 and December 2017. Of 23 957 participants, 12 510 were male. Men consistently presented with lower median CD4 count (period I-IV, P < .05) and higher median age (period I-III, P < .001) than women. From period I to IV, median age increased in women ( P < .0001), ART initiation time decreased in both sexes ( P < .001), and median CD4 remained <200 cells/µL in men. Advanced HIV disease and increasing age at presentation are persistent sex-specific trends which warrant innovative HIV testing strategies in both sexes.